TINJAUAN KRIMINALISASI PERBUATAN KOHABITASI DALAM PERPEKTIF HUKUM PIDANA - Patrecia Melenia Yoanda Kartodinudjo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The phenomenon of cohabitation or cohabiting is increasingly evident in people's lives, especially in Indonesia. Taboo acts have become increasingly evident with the times, living together in one house like husband and wife who have a household or family life but without a valid marriage bond. Indonesian society is increasingly becoming a modern society that does not want to be outdone by the times, but their notion of modernity is the opposite of where they live, namely Indonesia. Where in Indonesia the state considers the act to be a disgraceful act, violating the rules and values ??that exist and are inherent in oneself and the state. In the Criminal Code (WvS) by the Netherlands which had been absorbed and used by the Indonesian state as a basis for convicting or convicting someone who was proven guilty, it did not contain this cohabitation regulation, then the idea emerged to create its own legal product which was finally legalized in 6 December 2022 yesterday regarding the new Criminal Code. Which act of cohabitation is included in the offense in the new Criminal Code and is subject to criminal penalties for the perpetrator who committed the act. The purpose of making this journal is to find out what are the basic considerations for criminalization of cohabitation regulations